2013
DOI: 10.4081/hpr.2013.e28
|View full text |Cite
|
Sign up to set email alerts
|

Ten weeks of home-based exercise attenuates symptoms of chemotherapy-induced peripheral neuropathy in breast cancer patients

Abstract: The purpose of this investigation was to determine if a structured, home-based exercise program was beneficial to reduce symptoms of chemotherapy-induced peripheral neuropathy and improve quality of life (QOL). A total of 50 women who are breast cancer survivors and are listed in the Breast Cancer Registry of Greater Cincinnati database were recruited by mail. Participants were initially asked to complete the McGill QOL questionnaire and the Leeds Assessment of Neuropathic Symptoms and Signs, before beginning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 29 publications
(20 reference statements)
0
38
0
1
Order By: Relevance
“…Also clinical trial conducted on patients investigated the role of exercise in the management of peripheral neuropathy [ 71 ]. Two studies that tested a structured 10-12 weeks exercise programs (one supervised, the other home-based) found that exercise training reduces CIPN symptoms, such as unpleasant skin sensations, sensitivity related to neuropathic pain and the experience of coming on suddenly in bursts for no apparent reason [ 87 , 88 ].…”
Section: Physical Aspectsmentioning
confidence: 99%
“…Also clinical trial conducted on patients investigated the role of exercise in the management of peripheral neuropathy [ 71 ]. Two studies that tested a structured 10-12 weeks exercise programs (one supervised, the other home-based) found that exercise training reduces CIPN symptoms, such as unpleasant skin sensations, sensitivity related to neuropathic pain and the experience of coming on suddenly in bursts for no apparent reason [ 87 , 88 ].…”
Section: Physical Aspectsmentioning
confidence: 99%
“…Developing home-based interventions, are efficient for population groups in developing countries where lack of proper medical exposure accounts for widespread cancer-related morbidity and mortality (23). Wonders et al (61) have also reported that home-based interventions can indeed impart beneficial effects in cancer survivors by reducing the peripheral neuropathic symptoms and enhancing the quality of life. We propose that in a home-based scenario patients can be taught by medical experts to utilize established smartphone rhythmic auditory cueing applications, such as Walkmate (119) to train gait effectively.…”
Section: Prospective Role Of Music-based Therapies: External Auditorymentioning
confidence: 99%
“…This review was not limited to RCTs, but included 2 single-arm trials that did not meet our inclusion criteria. 20 , 76 Another recent integrative review concluded that exercise is “safe, feasible, and potentially effective for patients with CIPN” but that a definitive conclusion could not be drawn from the evidence available. 42 …”
Section: Physiotherapy For Chemotherapy-induced Peripheral Neuropamentioning
confidence: 99%